2005
DOI: 10.1007/s00464-004-8937-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbon dioxide pneumoperitoneum and wound closure technique on port site tumor implantation in a rat model

Abstract: This study suggests that closure technique may influence the rate of port site tumor implantation. The use of a CO2 pneumoperitoneum did not alter the incidence of port site tumor implantation at 7 days postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Povidone-iodine irrigation has been questioned, and peritoneal irritation secondary to this agent must not be underestimated [9, 3137]. Regarding suggestion 10, Burns and coworkers [21] demonstrated on an animal model that portsite tumor implantation was significantly increased ( P < 0.03) when only skin was closed compared with closure of all three layers [21]. The authors proved that closure technique may influence the rate of port-site tumor implantation [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Povidone-iodine irrigation has been questioned, and peritoneal irritation secondary to this agent must not be underestimated [9, 3137]. Regarding suggestion 10, Burns and coworkers [21] demonstrated on an animal model that portsite tumor implantation was significantly increased ( P < 0.03) when only skin was closed compared with closure of all three layers [21]. The authors proved that closure technique may influence the rate of port-site tumor implantation [21].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding suggestion 10, Burns and coworkers [21] demonstrated on an animal model that portsite tumor implantation was significantly increased ( P < 0.03) when only skin was closed compared with closure of all three layers [21]. The authors proved that closure technique may influence the rate of port-site tumor implantation [21]. For hand-assisted laparoscopic surgery, Chen and collaborators [38] recommend using a watertight bag model, not enlarging the surgical wound if there is resistance when extracting the surgical specimen and changing gloves before wound closure in order to avoid contamination with malignant cells [38].…”
Section: Discussionmentioning
confidence: 99%
“…29 Local application of cytotoxic agents, such as methotrexate and cyclophosphamide, is also found to be effective 30 • Suturing all port sites ≥10 mm 9,31 Burns et al 33 demonstrated on an animal model that port-site tumor implantation was significantly increased when only skin was closed compared with closure of all three layers. The authors proved that closure technique may influence the rate of port-site tumor implantation.…”
Section: Discussionmentioning
confidence: 99%
“…During this procedure, both the peritoneum and Gerota's fascia were opened, exposing the perirenal space to the extraperitoneal environment and intraperitoneum. A review of the literature reveals that closure of the fascia and peritoneum decrease the risk of tumor seeding and metastasis in experimental models [20, 21]. Furthermore, the literature shows that peritoneal defects may play an important role in tumor implantation and tumor metastasis [22].…”
Section: Discussionmentioning
confidence: 99%